Effect of operating parameters on the drilling behavior of Zr57.5Cu11.2Ni13.8Al17.5 bulk metallic glass. Issue 23 (20th November 2013) - Tariq, Naeem ul Haq; Muhammad, Ghulam; Awais, Hasan Bin
Abstract: Abstract : Zr-based bulk metallic glasses (BMGs) exhibit superior physical and chemical properties in comparison to their crystalline counterparts. In the present work, drilling behavior of Zr57.5 Cu11.2 Ni13.8 Al17.5 BMG was investigated at various operating conditions. Drilling was performed using high-speed steel (HSS) and carbide bits. Chip morphology, chip light emission, and burr formation at various drilling parameters were studied to achieve a feasible operating condition for drilling hole without light emission, chip clogging, and debris accumulation. Short spiral chip morphology which is considered ideal in the drilling process was observed at relatively low feed rate (1.5 mm/min) and medium spindle speed (1500 rpm). This also resulted in a small amount of molten debris around the entry hole. It was observed that at the same feed rate, the gradual increase in the speed of the HSS drill bit results in more light emission from the machining surface, whereas no light emission was observed in the case of the carbide drill bit at all drilling parameters.